The potential and status of renewable energy development in Malaysia - Abdullah W.S.W.; Osman M.; Kadir M.Z.A.A.; Verayiah R. (MDPI AG, 2023)
Energy policy; Natural gas; Conventional energy; Energy industry; Malaysia; Malaysian governments; Renewable energies; Renewable energy development; Renewable energy potentials; Research and development; Renewable energy resources